The Study of Biomechanics in Sports - Lestari, Indah; Yahya, Muhammad (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
Biomechanics is one of the main sciences of sports, when viewed from the origin it consists of two syllables, namely Bio and Mechanics which can be interpreted as the mechanics of living things in this case humans. So in terms of biomechanics is the study of the motion of living/inanimate objects and the forces that work and the resulting effects through a mechanical approach. While mechanics itself is part of the discussion in physics that studies how power can produce a certain motion as desired by athletics.